Uso de herramientas de tecnología de información y comunicación para elaborar y actualizar las principales causas de morbilidad en el cantón Yacuambi durante el 2012. - Regalado Aguirre, Kelly Soraya (2014)
The present study aims to establish the main causes of morbidity in the canton Yacuambi using tools of Information and Communication Technology (ICT) in order to generate statistical data, a descriptive study was conducted with design quantitative, sample corresponds to the medical records of 2012 of Subcentro de Salud 28 de Mayo and puestos de salud de Tutupali, La Esperanza and Jembuentza. ICT tools used were: Internet, email, Skype, telephone and computer with scanner. According to the response of rural doctors to perform the process communication barriers of physical type is presented. The main causes of morbidity in 2011 were: unspecified intestinal parasitosis, acute infections of the upper respiratory tract and dermatophytosis and in 2012 were: acute infections of the upper respiratory, intestinal parasitosis and unspecified diarrhea and gastroenteritis of presumed origin infectious.